Suicide in the Military: Understanding Rates and Risk Factors Across the United States' Armed Forces. (21st March 2019) - Pruitt, Larry D; Smolenski, Derek J; Bush, Nigel E; Tucker, Jennifer; Issa, Fuad; Hoyt, Timothy V; Reger, Mark A
Abstract: This paper presents data from the United States Department of Defense Suicide Event Report System for years 2012–2015 to detail descriptive, longitudinal rate data and risk factor profiles associated with military suicide. The annual findings were aggregated from all U.S. military suicide deaths and suicide attempts. Data elements included the most common method of suicide (firearms), most common behavioral health diagnoses (substance abuse/dependence), common life stressors (failed intimate–partner relationships), and an individual's history of operational deployment. Age- and sex-adjusted rates for the Services were compared with rates for the U.S. adult population. Results showed that the current reporting period (2015) is similar to patterns that have been observed over the preceding years and to patterns reported in the overall U.S. adult population. Suicide rates remain elevated but stable for both the Active and Reserve Components of the Military Services compared to historical levels observed prior to 2003. Finally, we discuss common errors and misinterpretations that can occur when analyzing surveillance data.